Isolation, characterization, and pathogenicity of Fusarium species causing crown rot of wheat - Ma, Guoping; Wang, Heng; Qi, Kai; Ma, Liguo; Zhang, Bo; Zhang, Yueli; Jiang, Hang; Wu, Xuehong; Qi, Junshan (Frontiers in Microbiology, 2024)
Fusarium crown rot (FCR) is one of the most important soilborne diseases affecting wheat production. To investigate the diversity of the pathogens associated with this disease, 199 diseased wheat samples were collected from 13 cities in Shandong province. In total, 468 isolates were obtained and were identified as 11 Fusarium species based on phylogenetic analyses with the translation elongation factor-1α (TEF-1α), RNA polymerase II largest subunit (RPB1), and RNA polymerase II second largest subunit (RPB2) gene sequences. Of these Fusarium isolates, 283 were identified as Fusarium pseudograminearum, and the remaining isolates were identified as F. graminearum (n=113), F. sinensis (n=28), F. acuminatum (n=18), F. incarnatum (n=13), F. ipomoeae (n=5), F. flocciferum (n=3), F. proliferatum (n=2), F. asiaticum (n=1), F. culmorum (n=1), and F. oxysporum (n=1), suggesting that F. pseudograminearum is the dominant pathogen of FCR of wheat in Shandong province.Pathogenicity tests demonstrated that all 11 Fusarium species could cause typical symptoms of FCR on wheat seedlings. Results of the study indicate that a greater diversity of Fusarium species can cause FCR of wheat in Shandong province than that has been previously reported. This is the first report globally of F. incarnatum, F. ipomoeae, and F. flocciferum as pathogens of FCR of wheat.